Public investments: Is there a golden rule separating "good" from "bad" debt? - Torben M. Andersen (EconPol Forum, 2023)
Across EU countries there is no general tendency for public investment to be crowded out by fiscal rules. The notion of investment in the public sector is different from the private sector, and it is problematic to base policy rules on the national account definition of investment. A Golden Rule allowing debt financing of public net investment requires a fundamental change in accounting principles to be applied consistently and raises fundamental implementation issues. Needs for government investment are increasing due to the green transition, energy supply disruption and digitalization, but do not require more complicated fiscal rules. Policy focus on investment can be increased by a continuous in-depth monitoring of public investment and/or separate expenditure targets for public consumption and investment
Keywords: 330